Whole-Body Vibration Training Increases Stem/Progenitor Cell Circulation Levels and May Attenuate Inflammation. (19th February 2020) - Jawed, Yameena; Beli, Eleni; March, Keith; Kaleth, Anthony; Loghmani, M Terry
Abstract: Introduction: Whole-body vibration training (WBVT) may benefit individuals with difficulty participating in physical exercise. The objective was to explore the effects of WBVT on circulating stem/progenitor cell (CPC) and cytokine levels. Methods: Healthy male subjects each performed three activities randomly on separate days: (1) standing platform vibration, (2) repetitive leg squat exercise; and (3) in combination. Pre- and post-activity blood samples were drawn. Cell populations were characterized using flow cytometry. Biomarkers were analyzed using enzyme-linked immunosorbent assays. Results: CPC levels increased significantly 21% with exercise alone (1465 ± 202–1770 ± 221 cells/mL; P = 0.017) and 33% with vibration alone in younger participants (1918 ± 341–2559 ± 496; P = 0.02). Angiogenic CPCs increased 39% during combined activity in younger (633 ± 128–882 ± 181; P = 0.05). Non-angiogenic CPCs increased 42% with vibration alone in younger (1181 ± 222–1677 ± 342; P = 0.04), but 32% with exercise alone in older participants (801 ± 251–1053 ± 325; P = 0.05). With vibration alone, anti-inflammatory cytokine interleukin-10 increased significantly ( P < 0.03), although inflammatory interleukin-6 decreased ( P = 0.056); tumor necrosis factor-alpha ( P < 0.01) and vascular endothelial growth factor levels increased ( P < 0.005), which are synergistically pro-angiogenic. Conclusions: WBVT may have positive vascular and anti-inflammatory effects. WBVT could augment or serve as an exercise surrogate in warfighters and others who cannot fully participate in exercise programs, having important implications in military health.